Effectiveness of capital assistance by zakat institution : Study among asnaf Parit Buntar, Perak - Norshafiqah, Daliyana (2021)
Capital assistance aims to help the poor and needy asnaf, from the zakat beneficiaries to the zakat payers and improve their quality of lives. It helps the asnaf get support to get on with life and help them out from the grip of poverty as much as possible. Capital assistance usually in productive assistance which assistance in the form of cash or equipment. The research aimed to give clearer picture on the effectiveness of capital assistance provide by zakat institution among asnaf especially in Parit Buntar, Perak. The research based on interview and research on previous study using qualitative method. The study was done with the cooperation from four capital assistance recipient and Majlis Agama Islam dan ‘Adat Melayu Perak (MAIPk) officers. Based on content analysis on primary and secondary data, the discussion of this paper is divided into three sections. First, this paper explore the effectiveness of capital assistance from recipient view. Second, this paper investigate the factors that influence the effectiveness of capital assistance and third, it identifies the challenges faced by zakat institution in capital assistance program. The finding of the study revealed that capital assistance program effective in transforming the status of asnaf from receipient to payer of zakat. The significant factor that influence the efficacy of capital assistance the attitude of the asnaf itself and encouragement from zakat institution.